Apache Solr 3 Enterprise Search Server : entrance your search with faceted navigation, result highlighting, relevance ranked sorting, and more /: entrance your search with faceted navigation, result highlighting, relevance ranked sorting, and more. (2011) - Unknown
No abstract available